2017
DOI: 10.1530/eje-17-0260
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of vascular invasion in differentiated thyroid carcinoma: a systematic review and meta-analysis

Abstract: Our study demonstrated a significant impact of VI on tumor recurrence and patient survival in DTC patients. The presence and extent of VI should be considered an adverse prognostic factor in DTCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
(68 reference statements)
3
25
0
1
Order By: Relevance
“…Our meta‐analysis results demonstrated that most of the clinicopathological behaviors of SVPTC are not statistically different from those of cPTC. However, this PTC variant was associated with an elevated risk for vascular invasion, which has recently been confirmed as a risk factor for tumor recurrence and patient mortality in differentiated thyroid carcinoma . As a consequence, SVPTC was found to have worse disease‐free survival in comparison to cPTC in our study.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Our meta‐analysis results demonstrated that most of the clinicopathological behaviors of SVPTC are not statistically different from those of cPTC. However, this PTC variant was associated with an elevated risk for vascular invasion, which has recently been confirmed as a risk factor for tumor recurrence and patient mortality in differentiated thyroid carcinoma . As a consequence, SVPTC was found to have worse disease‐free survival in comparison to cPTC in our study.…”
Section: Discussionsupporting
confidence: 52%
“…However, this PTC variant was associated with an elevated risk for vascular invasion, which has recently been confirmed as a risk factor for tumor recurrence and patient mortality in differentiated thyroid carcinoma. 36 As a consequence, SVPTC was found to have worse disease-free survival in comparison to cPTC in our study. Although the presence of vascular invasion in thyroid cancer is strongly associated with distant metastasis, we did not find a significantly increased risk for distant metastasis in SVPTC, most likely due to the small number of cases included in the analysis.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…In the 2015 AFIP atlas, FTC was classified into four prognostic groups: (i) minimally invasive FTC with capsular invasion; (ii) minimally invasive FTC with limited (<4 vessels) vascular invasion; (iii) minimally invasive FTC with extensive (≥4 vessels) vascular invasion; and (iv) widely invasive FTC . These two classifications highlighted the importance of vascular invasion in risk stratification of thyroid carcinomas . As FT‐UMP and WDT‐UMP were introduced in the thyroid tumor classification, evaluation of capsular and vascular invasion has become much stricter, and only definite invasion (Fig.…”
Section: Follicular Thyroid Carcinomamentioning
confidence: 99%
“…156 These two classifications highlighted the importance of vascular invasion in risk stratification of thyroid carcinomas. [157][158][159][160][161][162][163][164][165] As FT-UMP and WDT-UMP were introduced in the thyroid tumor classification, 1,32,33 evaluation of capsular and vascular invasion has become much stricter, and only definite invasion (Fig. 5a, b) is accepted for the diagnosis of FTC.…”
Section: Follicular Thyroid Carcinomamentioning
confidence: 99%